Prevalence of depressive disorders and treatment in China: a cross-sectional epidemiological study. (November 2021) - Lu, Jin; Xu, Xiufeng; Huang, Yueqin; Li, Tao; Ma, Chao; Xu, Guangming; Yin, Huifang; Xu, Xiangdong; Ma, Yanjuan; Wang, Limin; Huang, Zhengjing; Yan, Yongping; et al.
Summary: Background: In China, depressive disorders have been estimated to be the second leading cause of years lived with disability. However, nationally representative epidemiological data for depressive disorders, in particular use of mental health services by adults with these disorders, are unavailable in China. The present study, part of the China Mental Health Survey, 2012–15, aims to describe the socioeconomic characteristics and the use of mental health services in people with depressive disorders in China. Methods: The China Mental Health Survey was a cross-sectional epidemiological survey of mental disorders in a multistage clustered-area probability sample of adults of Chinese nationality (≥18 years) from 157 nationwide representative population-based disease surveillance points in 31 provinces across China. Trained investigators interviewed the participants with the Composite International Diagnostic Interview 3.0 to ascertain the presence of lifetime and 12-month depressive disorders according to DSM-IV criteria, including major depressive disorder, dysthymic disorder, and depressive disorder not otherwise specified. Participants with 12-month depressive disorders were asked whether they received any treatment for their emotional problems during the past 12 months and, if so, the specific types of treatment providers. The Sheehan Disability Scale (SDS) was used to assess impairments associated with 12-month depressive symptoms. Data-quality control procedures included logic check by computers, sequential recording check, and phone-call check by the quality controllers, and reinterview check by the psychiatrists. Data were weighted according to the age–sex–residence distribution data from China's 2010 census population survey to adjust for differential probabilities of selection and differential response, as well as to post-stratify the sample to match the population distribution. Findings: 28 140 respondents (12 537 [44·6%] men and 15 603 [55·4%] women) completed the survey between July 22, 2013, and March 5, 2015. Ethnicity data (Han or non-Han) were collected for only a subsample. Prevalence of any depressive disorders was higher in women than men (lifetime prevalence odds ratio [OR] 1·44 [95% CI 1·20–1·72] and 12-month prevalence OR 1·41 [1·12–1·78]), in unemployed people than employed people (lifetime OR 2·38 [95% CI 1·68–3·38] and 12-month OR 2·80 [95% CI 1·88–4·18]), and in people who were separated, widowed, or divorced compared with those who were married or cohabiting (lifetime OR 1·87 [95% CI 1·39–2·51] and 12-month OR 1·85 [95% CI 1·40–2·46]). Overall, 574 (weighted % 75·9%) of 744 people with 12-month depressive disorders had role impairment of any SDS domain: 439 (83·6%) of 534 respondents with major depressive disorder, 207 (79·8%) of 254 respondents with dysthymic disorder, and 122 (59·9%) of 189 respondents with depressive disorder not otherwise specified. Only an estimated 84 (weighted % 9·5%) of 1007 participants with 12-month depressive disorders were treated in any treatment sector: 38 (3·6%) in speciality mental health, 20 (1·5%) in general medical, two (0·3%) in human services, and 21 (2·7%) in complementary and alternative medicine. Only 12 (0·5%) of 1007 participants with depressive disorders were treated adequately. Interpretation: Depressive disorders in China were more prevalent in women than men, unemployed people than employed, and those who were separated, widowed, or divorced than people who were married or cohabiting. Most people with depressive disorders reported social impairment. Treatment rates were very low, and few people received adequate treatment. National programmes are needed to remove barriers to availability, accessibility, and acceptability of care for depression in China. Funding: National Health Commission and Ministry of Science and Technology of People's Republic of China. Translation: For the Chinese translation of the abstract see Supplementary Materials section.